Programação generativa como linguagem e comunicação: processos de rotinas de código executável como ferramenta de transmissão da informação - Bighetti, Vera Sylvia (2008)
The study, titled Generative programming as language and communication Executable code routine processes as an information transmission tool, proposes to investigate the context and the content of the aesthetic interface in generative communications in networks. The object of this study are the code/protocol concepts as means for new modes of reading and it is based on the methodological and conceptual presuppositions of J. Derrida (Grammatology), A.P. Galloway (Protocol), the ergodism of E. Aarseth, as well as on the elucidative and critical theories of P. Weibel, L. Manovich, M. Lovejoy, G. Beiguelman, and L. Santaella on the art of the code, on software art, net art, and communications and technology. In digital art, user interaction is the essence of the work; it depends on this for the work to have meaning, both that which was established by the artist and the one the interactor, or interagent, or fruitioner-operator will create. While in traditional media works of art remit us to contemplation, communicative action is indispensible in digital art: it is in the interactor s experience with the work that this takes place, an experience of interaction that requires real time feedback. After image manipulation, interactivity was the innovative factor in the use of computers in art.The reflection of this study implies in the possible identification of the principles for the Foundations of the Critical and Aesthetic Analysis of the Network Culture, in the relationship between the interface and interactivity produced by contemporaneous artists/designers. The aesthetic interface of network communications will be treated in the specificities of the cultural interface. I begin based on the development of a set of pieces I have been presenting, with specific characteristics of the foundations of generative art and algorithms as sets of processes to make calculations with reference to work carried out by Golan Levin, Giselle Beiguelman, Generator.X, Rob Myers, Olga Goriunova, Stanza, among others, to question the central concepts that drive this project, as well as the countless questions brought up by the production of art/design/communications of the network culture, particularly those that best represent the suppositions of post-modernity as the cornerstone of authorship, remixing, sampling, self-generative routines, and fractal complexity. The crossing of the theory of complexity and the systems explored by artists provide us space to analyze the context of generative art and its relationship with communication in networks